The information content of tax loss carryforwards: IAS 12 vs. valuation allowance - Vanessa Flagmeier (Arbeitskreis Quantitative Steuerlehre (arqus), 2017)
This is the first study that analyzes the predictive ability of deferred tax information under IFRS. I examine whether deferred taxes provide information about future tax payments and future performance, using a German sample of IFRS firms. The focus on tax loss carryforwards enables a separation of the two relations, testing on the one hand, the relation between recognized deferred tax assets and future tax payments and on the other hand, the relation between the non-usable part of tax losses and future earnings. I find significantly negative coefficients for both deferred tax items, indicating that higher recognized deferred tax assets are associated with lower future tax payments and higher non-usable tax loss carryforwards with lower future performance. Additionally, I compare the tax accounts' predictive ability for a matched German and US sample and find no significant differences between firms reporting under IFRS and US-GAAP. Taken together, the evidence suggests that deferred tax items for tax loss carryforwards reported under IFRS provide useful information about future outcomes and that this predictive ability does not differ significantly from firms reporting under US-GAAP.
Keywords: 330; deferred taxes; IAS 12; valuation allowance; tax loss carryforwards; tax footnote